Antifouling and antibacterial zwitterionic hydrogels as soft contact lens against ocular bacterial infections. (15th March 2022) - Zhang, Jing; Qian, Sunxiang; Chen, Lingdong; Wu, Minmin; Cai, Yuqing; Mou, Xiaozhou; Feng, Jie
Graphical abstract: Highlights: A new kind of zwitterionic hydrogels were prepared for soft contact lenses (CLs). Zwitterionic CLs exhibit much better antifouling properties than commercial CLs. Antibiotics were loaded in zwitterionic CLs via molecular imprinting technology. Zwitterionic CLs have antibacterial properties both in vitro and in vivo. The conjunctivitis model of rabbits' eyes was constructed. Abstract: Antifouling and antibacterial zwitterionic hydrogels were prepared and used as soft contact lens for ocular bacterial infections therapy. The zwitterionic hydrogels are mainly composed of zwitterionic segments and tuned by a small part of other hydrophilic and hydrophobic monomers for optimal properties, which achieve high transmittance of 94% in the range of visible wavelength, high water content, good water retention rate and stable dehydration-rehydration property. Moreover, even after five co-culture cycles with non-specific protein and bacteria, the zwitterionic hydrogels showed much better antifouling properties than the commercial contact lens (CL). Besides, functional monomer acrylic acid was incorporated in the zwitterionic hydrogels to load norfloxacin (NF) and control its release by molecular imprinting technology. Thus, the zwitterionic hydrogels have significant in vitro and in vivo bactericidal function. By constructing a conjunctivitis model of rabbits, we found that delivery of NF by the zwitterionic hydrogels had a better therapeutic outcome than delivery of NF through eye-drops. These results indicate that the zwitterionic hydrogels are competitive candidates for the application of wearing contact lens and ophthalmic drug delivery.